Women Language Used by the Main Character in the “Black Widow” Movie: Sociolinguistic Study - Amanda Putri Syarifudin; Hero Gunawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to identify the features of women language that are found and the dominant features of the women language in the utterances of the main character in the "Black Widow" movie based on Lakoff’s theory. This research was conducted using a qualitative descriptive method. The sources of the data for this research are the Black Widow movie and its movie script that has been downloaded. From the findings, there are only nine of ten features of women language found in Natasha’s utterances, those features are lexical hedges or fillers (16%), intensifiers (28%), ‘hypercorrect’ grammar (6,7%), ‘super polite’ forms (1,3%), avoidance of strong swear words (4%), emphatic stress (25,3%), tag question (4%), rising Intonation on declarative (6,7%) and empty adjectives (8%). Intensifier is the most dominating feature used in Black Widow movie with 28% of Natasha’s utterances, seen she wanted to attract attention while assuring the addressee with her statement.